International business - Dlabay, Les R.; Scott, James Calvert (Singapore Cengage Learning Asia Pte Lte, 2012)
This book provides the foundation for studying international business and conducting business in today's global environment. Students develop the appreciation, knowledge, skills and abilities to live and work in a global marketplace.
The world of international business -- Organizing for international business -- Managing in a global environment -- Information and production systems for global business -- Marketing in a global economy -- Global financial management.
Includes index.
Philippine edition.
Keywords: International business enterprises -- Study and teaching; International business enterprises -- Problems, exercises, etc; International trade -- Study and teaching; International trade -- Problems, exercises, etc; Globalization -- Study and teaching; Globalization -- Problems, exercises, etc